2022
DOI: 10.3390/ijerph19127336
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of Factors Associated with Intimate Partner Femicide: A Systematic Review

Abstract: There has been a growing concern about violence against women by intimate partners due to its incidence and severity. This type of violence is a severe problem that has taken the lives of thousands of women worldwide and is expected to continue in the future. A limited amount of research exclusively considers factors related only to these women’s deaths. Most focus on deaths of both men and women in an intimate partnership and do not provide precise results on the phenomenon under study. The necessity for an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 92 publications
(293 reference statements)
0
5
0
3
Order By: Relevance
“…About the second research question, the hierarchical logistic regression model results confirmed the perpetrators’ age role [ 4 , 6 , 12 ] and the law enforcement membership as significant individual risk factors for committing suicide after IPF; on the contrary, differently from other studies [ 3 , 6 ], our results did not highlight the possible role of the perpetrators’ mental and/or physical illness for IPFS. At the relational level, jealousy, quarrels, and violent behaviors in the couple were found as significant risk factors only for IPF, confirming the central role of the men’s possessiveness, and control over women as one of the main triggers in IPF cases [ 71 ]. Finally, at the contextual level, only the availability of a firearm to commit IPF seems to be significantly associated with IPFS.…”
Section: Discussionmentioning
confidence: 94%
“…About the second research question, the hierarchical logistic regression model results confirmed the perpetrators’ age role [ 4 , 6 , 12 ] and the law enforcement membership as significant individual risk factors for committing suicide after IPF; on the contrary, differently from other studies [ 3 , 6 ], our results did not highlight the possible role of the perpetrators’ mental and/or physical illness for IPFS. At the relational level, jealousy, quarrels, and violent behaviors in the couple were found as significant risk factors only for IPF, confirming the central role of the men’s possessiveness, and control over women as one of the main triggers in IPF cases [ 71 ]. Finally, at the contextual level, only the availability of a firearm to commit IPF seems to be significantly associated with IPFS.…”
Section: Discussionmentioning
confidence: 94%
“…Múltiples trabajos han tratado de identificar factores que aumenten la probabilidad de sufrir violencia de género no letal, en general, y de sufrir una agresión mortal, en particular. En este sentido, aunque el feminicidio afecta a mujeres diversas (Consejo General del Poder Judicial, 2021), existen determinadas características y circunstancias que pueden colocar a ciertas mujeres en una situación de mayor vulnerabilidad, tal y como revelan múltiples estudios (Campbell, et al, 2003;Campbell et al, 2007;Garcia-Vergara et al, 2022;Spencer y Stith, 2018).…”
Section: A Vulnerabilidad De Las Mujeres Víctimas De Violencia De Parejaunclassified
“…De entre estas situaciones, destaca la ruptura de la pareja. La ruptura de la relación supone un estresor importante que puede dar lugar a episodios de violencia o incrementarla en caso de que ya existiera (e.g., Johnson, 2011), así como aumentar el riesgo de feminicidio (e.g., Fernández-Teruelo, 2013;Garcia-Vergara et al, 2022). Los estudios destacan que el proceso de separación puede aumentar hasta diez veces el riesgo de feminicidio (Campbell et al, 2003;Matias et al, 2019), destacando el estudio de Kivisto (2015), que concluyó que entre el 20%-30% de los feminicidios podrían ser producidos por la propia separación.…”
Section: B Situaciones Que Aumentan El Riesgo De Violencia De Pareja ...unclassified
See 1 more Smart Citation
“…These data suggest that intimate partner relationships can involve vulnerability and risk for women, and even end in murder [ 36 ]. Globally, a woman or girl is killed by a member of her family every 11 min.…”
Section: Gender-based Violence In Ecuador and Argentinamentioning
confidence: 99%